HUBUNGAN SELF-REGULATED LEARNING DENGAN PRESTASI AKADEMIK MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS TEKNOLOGI SUMBAWA - Abdika Tulus Sukmawansyah; Lukmanul Hakim; Roni Hartono (JURNAL PSIMAWA, 2019)
This research aims to know the relationship between self-regulated learning and academic achievement of students. This research used quantitative descriptive approach. The technique of taking sampling is purposive sampling. Withdrawing sampling used Slovin formula and determining sampling representatively were conducted by using cluster sampling. The sample of this research is seventy three students of psychology department in Sumbawa University of Technology. The data of the research was carried out by using instrumental research called self-regulated learning dan academic achievement sheet. The instrument of reliability test using validity constrast based on factor analysis. The result of this research showed that there are positive correlations between self-regulated learning and academic record by value of co-efficiency correlation 0,420 with p value = 0,0001/ p < 0,05 which means the higher it is self-regulated learning of students so the better it is academic achievement, and vice versa. The lower self-regulated learning of students so the lower academic achievement of students. Based on the research output, generally self regulated learning of student faculty of psychology be on average category and their academic achievement be on high level. Self regulated gives effective support on academic record by 17,7 % and 82,3 % was affected by other factors out of this research issues.